piRNA pathway evolution beyond gonad context: Perspectives from apicomplexa and trypanosomatids - Horjales, S.; Li Calzi, M; Francia, M. E.; Cayota, A.; Garcia-Silva, M. R. (Frontiers in Genetics, 2023)
piRNAs function as genome defense mechanisms against transposable elements insertions within germ line cells. Recent studies have unraveled that piRNA pathways are not limited to germ cells as initially reckoned, but are instead also found in non-gonadal somatic contexts. Moreover, these pathways have also been reported in bacteria, mollusks and arthropods, associated with safeguard of genomes against transposable elements, regulation of gene expression and with direct consequences in axon regeneration and memory formation. In this Perspective we draw attention to early branching parasitic protozoa, whose genome preservation is an essential function as in late eukaryotes. However, little is known about the defense mechanisms of these genomes. We and others have described the presence of putative PIWI-related machinery members in protozoan parasites. We have described the presence of a PIWI-like protein in Trypanosoma cruzi, bound to small non-coding RNAs (sRNAs) as cargo of secreted extracellular vesicles relevant in intercellular communication and host infection. Herein, we put forward the presence of members related to Argonaute pathways in both Trypanosoma cruzi and Toxoplasma gondii. The presence of PIWI-like machinery in Trypansomatids and Apicomplexa, respectively, could be evidence of an ancestral piRNA machinery that evolved to become more sophisticated and complex in multicellular eukaryotes. We propose a model in which ancient PIWI proteins were expressed broadly and had functions independent of germline maintenance. A better understanding of current and ancestral PIWI/piRNAs will be relevant to better understand key mechanisms of genome integrity conservation during cell cycle progression and modulation of host defense mechanisms by protozoan parasites.